Pistachio nut allergy: An updated overview - Costa, Joana (2019)
Pistachio nut (Pistacia vera) is highly appreciated for its organoleptic characteristics and potential health benefits. However, this tree nut is also responsible for triggering moderate to severe IgE-mediated reactions in allergic individuals. Currently, pistachio nut allergy has gained some special attention, mainly due to its intrinsic relation with cashew nut allergy. Like for other nuts, the prevalence of pistachio nut allergy seems to be increasing at a global scale. Until now, there are five allergenic proteins officially listed for pistachio nut (Pis v 1, Pis v 2, Pis v 3, Pis v 4 and Pis v 5). Relevant data on their biochemical classification has become available, enabling establishing a correlation with the respective clinical symptoms. The establishment of an effective allergen risk assessment is a key issue for the food industry, policy makers and regulatory agencies. Thus, the availability of fast, specific and sensitive methods to detect trace amounts of allergens in processed foods is crucial. In the specific case of pistachio nut, there are some protein- and DNA-based methods for its detection/quantification in foods, which can aid to verify label information. Accordingly, all relevant research advances on this topic were summarised, updated and critically discussed in this review.